Effect of intracoronary bone marrow-derived mononuclear cell injection early and late after myocardial infarction on CMR-derived myocardial strain. (1st July 2020) - Gastl, M.; Sürder, D.; Corti, R.; Faruque Osmany, D.M.M.; Gotschy, A.; von Spizcak, J.; Sokolska, J.; Metzen, D.; Alkadhi, H.; Ruschitzka, F.; Kozerke, S.; Manka, R.
Abstract: Background: Studies indicate no clear impact of intracoronary injection of bone-marrow unselected mononuclear cells (BM-MNC) after acute myocardial infarction (AMI) on left-ventricular function (LVEF). Strain parameters by cardiovascular magnetic resonance (CMR) have been proposed to be more sensitive to functional changes of the heart. The aim of the present study was to assess changes of global longitudinal (GLS) and circumferential strain (GCS) in a group of patients treated with BM-MNC after AMI. Methods: One-hundred and forty-nine patients with successfully reperfused AMI and LV dysfunction (LVEF<45%) were retrospectively included into this sub-study of the SWISS-AMI multicentre trial. Patients were divided into control ( N = 54), early (5–7 days after AMI, N = 51) and late BM-MNC treatment groups (3–4 weeks, N = 44). The endpoint was the change of GLS and GCS as obtained from cine sequences 4 and 12 months after AMI using feature tracking algorithm. Results: In unadjusted analyses, the absolute change of GLS for the early treatment group from baseline to 4 months was 2.5 ± 4.3 ( p < 0.01), to 12 months 2.7 ± 5.7% ( p = 0.004). For late treatment, it was 1.5 ± 4.0% ( p = 0.039, 4 months) and 2.5 ± 5.6% ( p = 0.015, 12 months). For controls 0.7 ± 4.7% ( p = 0.378), 0.8 ± 3.9% ( p = 0.253) respectively. Adjusting for different baseline values, neither an overall treatment effect (both time-points) of BM-MNC nor a treatment time-related (only early or late) effect could be shown for all functional parameters. Conclusions: Among patients after AMI with successful reperfusion and LV dysfunction, intracoronary infusion of BM-MNC early or late after AMI did not improve global strain parameters at 4- or 12-months follow-up. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00355186 . Highlights: Unadjusted analysis revealed an impact of early, less late, BM-MNC injection on GLS 4 or 12 months after AMI. GCS and LVEF showed no improvement after intracoronary BM-MNC. Accounting for different baseline values, no treatment effect of BM-MNC on all strains remained. Dividing groups by certain predictors, BM-MNC could not improve functional parameters as well.